Metabolic Reprogramming and Cell Adhesion in Acute Leukemia Adaptation to the CNS Niche - Sharma, Nitesh D.; Keewan, Esra’a; Matlawska-Wasowska, Ksenia (Frontiers in Cell and Developmental Biology, 2021)
Involvement of the Central Nervous System (CNS) in acute leukemia confers poor prognosis and lower overall survival. Existing CNS-directed therapies are associated with a significant risk of short- or long-term toxicities. Leukemic cells can metabolically adapt and survive in the microenvironment of the CNS. The supporting role of CNS microenvironment in leukemia progression and dissemination has not received sufficient attention. Understanding the mechanism by which leukemic cells survive in the nutrient-poor and oxygen-deprived CNS microenvironment will lead to the development of more specific and less toxic therapies. Here, we review the current literature regarding the roles of metabolic reprogramming in leukemic cell adhesion and survival in the CNS.